PENERAPAN METODE JIGSAW UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR FISIKA KELAS XII MAN 15 JAKARTA - Irawati, Intan (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
This study was conducted to prepare the grade XII’s students in facing the Physics National Examination. The preparation was done with apply Jigsaw method in physics teaching learning. Its’ goal was to increase students’ motivation and achievement physics test. The place of study was in Senior Islamic High School State (MAN) 15, Ciracas, East Jakarta and the subject of this study was 22 students physics class XII science-1 school year 2013-2014. The study was Classroom Action Research (CAR) in two cycles. The data was collected by observation students and teacher sheets, questionnaire and achievement test. The data was analyzed by descriptive statistic. The result of study was increasing average test score 123% from 32.72 to 72.08. The questionnaire analyzed showed that almost all of students (91.7%) felt motivate and enthusiasm in learning physics after the study and also the students felt more confidence in facing Physics National Examination. Keywords: achievement, Jigsaw method, motivation, physics.